2005
DOI: 10.1089/dia.2005.7.28
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of Algorithms and Challenges in the Development of a Closed-Loop Artificial Pancreas

Abstract: The development of an artificial pancreas is placed in the context of the history of the field of feedback control systems, beginning with the water clock of ancient Greece, and including a discussion of current efforts in the control of complex systems. The first generation of artificial pancreas devices included two manipulated variables (insulin and glucose infusion) and nonlinear functions of the error (difference between desired and measured glucose concentration) to minimize hyperglycemia while avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
169
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(176 citation statements)
references
References 41 publications
0
169
0
7
Order By: Relevance
“…Several are based on mathematical models and designed as proportional integral derivative or model predictive control (4 -7); others are based on fuzzy logic (8). However, as was noted by Hovorka et al (9), a number of challenges remain to be solved before the artificial ␤-cell is realized: one of the critical challenges is the regulation of glucose levels after a meal (10). The meal challenge can be met, in principle, by three different approaches.…”
mentioning
confidence: 99%
“…Several are based on mathematical models and designed as proportional integral derivative or model predictive control (4 -7); others are based on fuzzy logic (8). However, as was noted by Hovorka et al (9), a number of challenges remain to be solved before the artificial ␤-cell is realized: one of the critical challenges is the regulation of glucose levels after a meal (10). The meal challenge can be met, in principle, by three different approaches.…”
mentioning
confidence: 99%
“…A variety of PID control strategies have been developed for diabetes and described in survey papers and articles [7][8][9]11,[37][38][39]. Most of the related evaluations have been based on simulation studies but experimental applications to dogs and humans have also been reported.…”
Section: A Pid Switching Control Strategymentioning
confidence: 99%
“…The tuning strategy used in this research was based on minimization of the discrete version of the integral absolute error for a meal challenge: (11) where IAE (mg min/dL) is the integral absolute error, t ∞ is the duration of the simulation, e = G sp − G where G sp is the setpoint (mg/dL), and Δt is the sampling period (5 min). Based on extensive simulations for different meal sizes, the optimal value of τ 4 appeared to be quite constant, and a value of τ 4 = 0.3 min was satisfactory in all cases.…”
Section: Feedforward Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, hypoglycemia is considered as one of the major limiting factors in achieving tight glycemic control in T1DM (Cryer (2008)). With the inability of conventional therapy to achieve satisfactory glycemic control, and the development in continuous glucose monitoring (CGM) systems and the increasing use of insulin pumps, the idea of developing an artificial pancreas is viewed as the ideal solution for glycemic control in T1DM (Bequette (2005); Hovorka et al (2006); Kumareswaran et al (2009)). The artificial pancreas is an automated closed-loop system that maintains blood glucose levels within the desired range and prevents hypoglycemia, while minimizing or eliminating the need for patient intervention.…”
Section: Introductionmentioning
confidence: 99%